Who are the most powerful people in music? Jay Z? Kanye? Beyoncé? No, it’s old white men (the Guardian, 2016)
The 2016 Billboard Power 100 is dominated by white men born before Elvis had a hit. This isn’t only a problem of representation – it’s also bad for the industry